Evaluation Arabic language curricula content at the intermediate stage in light of the requirements for enhancing personality (Analytical study) - Otaif, Yahya Mansour (Journal of Educational and Psychological Sciences, 2021)
The aim of the research is to evaluate the content of the Arabic language curriculum at the intermediate stage in light of the requirements of personality enhancement. To achieve this goal, the researcher used the descriptive approach based on content analysis, and prepared a list of personal enhancement requirements. This list was used in preparing a card for analyzing the content of the curriculum, and it included three main requirements, And (47) sub-clauses, and the research sample consisted of the Arabic Language Book ("Lughati Al Khalidah") in its first and second semesters of the year 2018/2019, and the results of the research showed after adjusting the study tools (List of Personal Enhancement Requirements, Content Analysis Card), and to make sure of their sincerity and consistency that Family requirements and not Social accounted for 33% and 35.4% in the first and second semester, respectively, from the content of the paragraphs included in the content of the Arabic language curriculum for the first and second semester respectively, and the self-requirements came in at 25.8%, 35% in the first and second semester, respectively, While the national and economic requirements came in at 6.5% and 30.3% in the first and second semester, respectively, and in light of those results, the study presented a number of recommendations and proposals.